PERANCANGAN TATA LETAK FASILITAS RUANG PEMERIKSAAN KESEHATAN MENGGUNAKAN ACTIVITY RELATIONSHIP CHART - Rohimah, Anni; Istiyono, Yogi Priyo; Fhatonah, Nuriyatul; Pratiwi, Dina; Ghozali, Ahmad Sulthon; Rasydy, La Ode Akbar; Kuncoro, Banu; Sulistyo, Suryo (Jurnal Inkofar, 2023)
Health examinations are a program held by Muhammadiyah A.R. Fachruddin University. One of the health check activities carried out was a free health check in the context of the regional musda and the inauguration of the muhamamadiyah regional management of tangerang regency. There are no guidelines or guidelines used in preparing the parts in the health examination room. The layout is still based on space availability without paying attention to the level of importance of the relationship between parts. The method used in preparing the free health examination layout is the activity relationship chart (ARC) assisted by BLOCPLAN software and followed by simulation using promodel. From the simulation, it is known that the utilization of the tension room is 79,87 and the utilization of the gcu room is 79,56.